Sistem Pendukung Keputusan Pemilihan Laptop Dengan Menggunakan Metode Topsis - Hertyana, Hylenarti; Mufida, Elly; Kaafi, Ahmad Al (LPPM UNIKA Santo Thomas, 2021)
The rapid development of technology, especially in the digital field, has had a huge influence on the development of laptop features and specifications today. With the development of increasingly diverse features and specifications, it often makes users confused in choosing a laptop that suits user needs. Based on this, the authors are interested in creating a decision support system to assist users in choosing a laptop that fits the desired criteria using the Topsis method. The type of data used by the author is primary data obtained through interviews and direct observation of laptop users. The purpose of this study is to assist laptop users in choosing a laptop that suits their needs. There are 10 criteria obtained based on observations and interviews, namely price (C1), RAM (C2), Hard drive (C3), processor (C4), screen size (C5), VGA (C6), battery (C7), Laptop Weight (C8), and Warranty (C9). Secondary data were obtained through literature study and scientific writing related to laptop selection and the TOPSIS method. This research produces output that meets the objectives, which can assist users in choosing the laptop that best suits their needs and can facilitate users in the decision-making process so as to produce accurate, effective and efficient information.